Instructional Process and Concepts in Theory and Practice 2016
DOI: 10.1007/978-981-10-2519-8_7
|View full text |Cite|
|
Sign up to set email alerts
|

English Language Teaching

Abstract: I certify that this thesis satisfies the requirements as a thesis for the degree of Master of Arts in English Language Teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The results also underscored the importance of teachers' overall perceptions of technology, technological experience, skill, and competence, and the cultural environment that surrounds the introduction of IT into schools and language institutes and shapes attitudes towards computer technology (Sarangi & Candlin, 2010). (Bozoğlan & Yılmaz, 2016) investigated the use of multi-media technology in language teaching. The study showed that the students' motivation and attention were significantly influenced by the use multi-media-based class since it helped the students deal with practical knowledge towards then use multi media-based classroom in learning foreign language via communication with other students.…”
Section: Introductionmentioning
confidence: 99%
“…The results also underscored the importance of teachers' overall perceptions of technology, technological experience, skill, and competence, and the cultural environment that surrounds the introduction of IT into schools and language institutes and shapes attitudes towards computer technology (Sarangi & Candlin, 2010). (Bozoğlan & Yılmaz, 2016) investigated the use of multi-media technology in language teaching. The study showed that the students' motivation and attention were significantly influenced by the use multi-media-based class since it helped the students deal with practical knowledge towards then use multi media-based classroom in learning foreign language via communication with other students.…”
Section: Introductionmentioning
confidence: 99%